(untitled) (Biological Sciences - PJSIR, 2007)
This study was aimed at determini ng the physical (pH, TDS, TSS) and ch emical (ammon ia, 8005 , COD, chl orid e, cyanid e, detergen ts, phenols and sulphate) parameters as wel l as heavy metal s (As, Cd, Cu , Cr, Pb, Ni , and Zn) present i n Malir ri ver water, so as to id entify the ex tent of poll ution . The average resu l ts of each parameter of 10 different sites were compared w i th N ational Envi ronmental Qual i ty Standards (NEQS). It was fou nd th at Mal i r river w ater quali ty meet s on l y some of the N EQS. Vari abl e quantitie s of different heavy metals were also found . It can be concluded that the conti nuous discharge of Malir river at Gizri creek plays an important role resulti ng in reduced biodiversity.